Borderline personality disorder and bipolar disorder comorbidity in suicidal patients : diagnostic and therapeutic challenges - Marčinko, Darko (Array, 2009)
Suicidality is one of the great challenges in contemporary psychiatry. Suicidal patients are often misdiagnosed in clinical practice. It is very important to evaluate possible comorbidity in diagnostic assessment of suicidal patients. Although the primary treatment for patients with BPD is psychotherapy, pharmacotherapy is a core component for the treatment of comorbid conditions such as bipolar disorder. Because of heterogeneity of the BPD, pharmacologic treatment has evolved to some particular dimensions of BPD rather than the disorder in its entirety. The dimensions include affective instability, impulsive aggression and identity disturbance. Effective medication management reduces the overall suffering of the patient and enables to make greater use of psychotherapeutic interventions which is very important for BPD patients with BD comorbidity.